Light-stimulated carrier dynamics of CuInS2/CdS heterotetrapod nanocrystals. Issue 18 (27th April 2016) - Sakamoto, Masanori; Inoue, Koki; Okano, Makoto; Saruyama, Masaki; Kim, Sungwon; So, Yeong-Gi; Kimoto, Koji; Kanemitsu, Yoshihiko; Teranishi, Toshiharu
Abstract : We synthesized a heterotetrapod composed of a chalcopyrite( ch )-CuInS2 core and wurtzite( w )-CdS arms and elucidated its optical properties and light-stimulated carrier dynamics using fs-laser flash photolysis. Abstract : We synthesized a heterotetrapod composed of a chalcopyrite( ch )-CuInS2 core and wurtzite( w )-CdS arms and elucidated its optical properties and light-stimulated carrier dynamics using fs-laser flash photolysis. The CuInS2 /CdS heterotetrapod possessed quasi-type II band alignment, which caused much longer-lived charge separation than that in the isolated CuInS2 nanocrystal.